2021
DOI: 10.1186/s42836-020-00063-3
|View full text |Cite
|
Sign up to set email alerts
|

Home physiotherapy with vs. without supervision of physiotherapist for assessing manipulation under anaesthesia after total knee arthroplasty

Abstract: The aim of this retrospective cohort study was to compare home physiotherapy with or without supervision of physiotherapist for assessing manipulation under anaesthesia after total knee arthroplasty. Methods A total of 900 patients (including 810 females and 90 males) who had undergone total knee arthroplasty were divided into group A (n = 300) and group B (n = 600). Patients in group A had home physiotherapy on their own after discharge from hospital. The physiot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 32 publications
0
1
0
Order By: Relevance
“…Regarding the other short-term outcomes, no differences were found with regard to lower extremity strength, knee flexion ROM, or patient-reported quality of life. Arthrofibrosis and the possible requirement for manipulation under anesthesia (MUA) remain a chief concern of proponents of supervised PT after surgery [27]; however, studies that examined MUA rates following surgery demonstrated no differences between the supervised and home PT cohorts [14,[16][17][18]. Finally, no long differences were observed in any of the examined outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…Regarding the other short-term outcomes, no differences were found with regard to lower extremity strength, knee flexion ROM, or patient-reported quality of life. Arthrofibrosis and the possible requirement for manipulation under anesthesia (MUA) remain a chief concern of proponents of supervised PT after surgery [27]; however, studies that examined MUA rates following surgery demonstrated no differences between the supervised and home PT cohorts [14,[16][17][18]. Finally, no long differences were observed in any of the examined outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…Earlier evidence revealed that frequent physiotherapist's instruction helps the patients improve knee exercises and recovery outcomes. 60 Thus, HCPs should explore establishing a post-discharge joint exercise guidance program based on physiotherapist.…”
Section: Discussionmentioning
confidence: 99%